The Ideas of Bloom’s Taxonomy in a Fifteenth-Century Treatise in Sri Lanka - Marikar, Faiz; Zayan, Ahamed (Educational Challenges, 2024)
Purpose. The purpose of this article is to study the relationship between Bloom’s Taxonomy and Kawyasekara. According to some, the first instance of Bloom’s Taxonomy was recorded by Benjamin Bloom in 1956, while Kawyasekara was written by Thotagamuwe Sri Rahula Thera in 1449. Methodology. Modern concepts of three hierarchical models, which differ from other types of educational concepts, did not develop until the fifteenth century, according to the critics. In this paper, it is shown how the concept we now refer to as Bloom’s Taxonomy was first presented in a similar manner in a text from the Kotte Era in Sri Lanka, written in the fifteenth century by Thotagamuwe Sri Rahula Thera. Results. This manuscript demonstrates that Thotagamuwe Sri Rahula Thera deserves praise for distinguishing educational notions from other kinds of educational conceptions. Thotagamuwe Sri Rahula Thera categories, which were much more recently discovered, are given special consideration. Conclusions. This document considering contemporary scientific findings and pedagogy exposes instructional ideas that have been around for centuries. These findings’ theoretical and clinical ramifications are also examined.